Systematic literature review on the supply chain agility for manufacturer and consumer. (17th January 2021) - Du, Yuying; Hu, Xia; Vakil, Ka
Abstract: For a company to survive in the long run, it is necessary to attract enough customers to generate profitability. Since the high uncertainty in organizations requires a more rapid response to customers' needs, agility is a critical success factor for today's manufacturing enterprise. To be competitive, enterprises must integrate their supply chains more effectively and forge close memberships with customers and suppliers more quickly. Therefore, the current study attempts to understand how supply chain agility has evolved. We have used a systematic literature review approach to examine the current state of the art and identify potential research gaps. It has indicated how companies can form and preserve competitive advantages in turbulent environments between manufacturers and consumers. From the outcomes, it can be observed that the developed supply chain agility has positive impacts on the sales of companies, velocity to market, profitability, market share and consumers' satisfaction. Also, the investigations showed that the supply chain agility management needs persistent planning. Allotment of the resources to the agility aspects' improvement might help companies increase the influence of such investments. Our investigation highlights the tactics for better readiness to attain supply chain agility that is the central part of electronic firms' competency in an emerging market.